COMPARISON OF THE EFFECT OF SUXXX, V-POXXX FUEL AND THEIR MIXTURES ON R15 MOTORCYCLE ENGINE PERFORMENCE - Wahid , M. Luqman; Firdaus , Rachmat (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: With the increase in motorcycle usage worldwide, optimizing engine performance through fuel selection has become a focus, as fuel type significantly impacts torque, power, and specific fuel consumption. Specific Background: Public motorcycle transportation options include various fuel types, such as suxxx and v-poxxx, as well as blends with ethanol, which are commonly used for enhanced engine efficiency. Knowledge Gap: There is limited research directly comparing the performance impacts of suxxx, v-poxxx, and their mixtures, especially with ethanol, on motorcycles over a range of RPMs. Aims: This study aims to evaluate the differences in motorbike performance using pure suxxx, v-poxxx, a 50-50 blend of suxxx and v-poxxx, and an 85-15 blend of suxxx and ethanol by examining torque, power, and specific fuel consumption (SFC) on an R15 motorbike through dynotest trials. Results: Findings indicate that v-poxxx, with its higher octane level, provides superior torque, power, and SFC compared to suxxx and mixed fuels, especially at low and high RPMs. Meanwhile, the 85% suxxx and 15% ethanol blend achieves the best SFC but has slightly lower torque and power at specific RPMs compared to v-poxxx. Novelty: This study provides comparative insights into the effectiveness of mixed ethanol fuels in motorcycles, identifying performance variances across a range of RPMs, which is less explored in the context of motorcycle engines. Implications: The results suggest that high-octane fuels enhance engine performance, while ethanol mixtures could serve as efficient alternatives for fuel savings. These insights are valuable for consumers and manufacturers aiming to optimize fuel usage for different riding conditions.